PSYCHOLOGICAL ASPECTS OF AESTHETIC RHINOPLASTY - Скрипніков, А.М.; Животовська, Л.В.; Боднар, Л.А.; Шиндер, В.В. (World of Medicine and Biology, 2015)
The analysis of scientific literature showed that the characteristics of patients seeking to plastic surgeon for aesthetic rhinoplasty are studied in recent years actively. It is proved that these patients have some features of mental state and even mental disorders that can affect psychological result of surgery and require medication and psychological adjustment. The analysis of scientific literature suggests a certain degree of congruence of factors that are likely to be predictors of adverse effects of the operation, namely demographic factors: male gender, young age (exact age is not reported); psychological/psychiatric factors: depression or anxiety, dysmorphophobia, personality disorder; personal problems, reasoned belief in the need of cosmetic surgery to save the relationship or eliminating differences between partners; unrealistic expectations regarding the results of operations; dissatisfaction with the results of previous surgery and minimum deformations.
Keywords: cosmetic defects and deformations of the nose; aesthetic rhinoplasty